Effects of Withania somnifera on Cortisol Levels in Stressed Human Subjects: A Systematic Review - Della Porta, Matteo; Maier, Jeanette A.; Cazzola, Roberta (Nutrients, 2023)
Background: Withania somnifera (WS), a popular medicinal plant of the Solanaceae family, contains active ingredients with antioxidant, anti-inflammatory, immunomodulatory, and anti-stress activities. However, its precise mechanisms of action and optimal use as a supplement are not yet fully understood. The objective of this systematic review is to assess the impact of WS supplementation on cortisol levels in stressed humans by analyzing clinical trials conducted prior to May 2023. Methods: The assessment was carried out following the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) by exploring the databases of EMBASE, PubMed, Google Scholar, CENTRAL, and Scopus. Results: Of the 4788 articles identified, only 9 studies met the selection criteria. The selected studies varied in terms of design, results, formulations, dosages, and treatment duration (30–112 days), and involved subjects with varying degrees of stress. WS supplementation decreases cortisol secretion with no significant adverse effects. Nonetheless, none of the studies evaluated the potential impact of cortisol reduction on adrenal function and long-term effects. Conclusions: Brief-term supplementation with WS appears to have a stress-reducing effect in stressed individuals. However, since the long-term effects of WS supplementation are not yet fully understood, WS supplements should be used under medical supervision.